(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article reflects on the expression of the evaluation SEMAS in the content aspect of the lexeme. Grade SEMAS lexemes: noun lexemes, adjective lexemes, and verb lexemes; grammatical suffixes have served to represent a positive, negative, or neutral grade relationship.